Differences in serum concentration with valproate oral solution versus delayed-release divalproex in an adherent patient - Davis Erica A. K. PharmD, BCPS, BCPP (American Association of Psychiatric Pharmacists, 2023)
Background Several different formulations of valproic acid derivatives are available in the United States. Although these formulations have different absorption characteristics, they are believed to be interchangeable, with the exception of the extended-release product. Case Report A 31-year-old African American man with schizoaffective disorder was started on fluphenazine concentrate and valproate oral solution on admission to an inpatient unit. A 12-hour steady-state concentration, drawn on 1000 mg/day, resulted in 40.8 mg/L, and the dose continued to be titrated. Despite increasing doses, confirmed medication adherence, and accurate lab sampling, his concentrations remained low: 60.3 and 60.1 mg/L on 1500 mg/day, and 65.6 mg/L on 1750 mg/day. He was switched to divalproex delayed-release tablets, and his dose was increased to 2000 mg/day. Follow-up 12-hour steady-state concentrations were significantly higher, at 126.6 and 113.8 mg/L. It is theorized that the formulation of divalproex/valproic acid is what contributed to these differences in concentrations. Discussion Valproic acid formulations are considered to be interchangeable, and several studies have demonstrated that chronic psychiatric inpatients stabilized on delayed-release divalproex may be safely switched to valproate oral solution without changes in psychiatric stability. This case demonstrates a significant difference in serum drug concentrations when switching from valproate oral solution to divalproex delayed-release tablets.